Evaluation of Excavator CAT 330 GC and Mitsubishi Fuso 220 PS Fleet Efficiency The Overburden Removal Target in Pit 2 of PT. Kurnia Alam Investama - Andri Van Deni; Heri Prabowo (CIVED, 2025)
Overburden removal is a critical determinant of production continuity in open-pit coal mining, yet inefficiencies in equipment utilization frequently hinder the achievement of production targets. At PT Kurnia Alam Investama, a monthly overburden stripping target of 150,000 BCM for February 2025 was established, to be achieved using two equipment fleets with a planned capacity of 75,000 BCM/month per fleet. However, preliminary observations indicate a discrepancy between planned and actual production, highlighting the need for a systematic evaluation of equipment performance and fleet compatibility. This study aims to assess the productivity and operational synchronization of a CAT 330 GC excavator and Mitsubishi Fuso 220 PS 6x4 HD dump trucks through cycle time analysis, productivity estimation, and match factor evaluation. The results show that actual productivity reached 67,150.72 BCM/month for the excavator and 52,407.4 BCM/month for the hauling units, both below the production target. The average cycle times were recorded at 0.343 minutes for the excavator and 5.39 minutes for the dump trucks. The calculated match factor (MF < 1) indicates an imbalance in the loading–hauling system, resulting in excavator idle time due to insufficient truck availability. The findings reveal that equipment condition and operator performance are the dominant factors affecting productivity losses. This study emphasizes the importance of fleet balancing, cycle time optimization, and operational improvements to enhance equipment utilization and achieve production targets efficiently.